2008
DOI: 10.1002/ejic.200800876
|View full text |Cite
|
Sign up to set email alerts
|

Generation of SmII Reductants Using High Intensity Ultrasound

Abstract: Ultrasound (20 kHz) was used to prepare samarium(II) diiodide (SmI2), samarium(II) dibromide (SmBr2), and samarium(II) triflate (SmOTf)2. The method described herein provides a straightforward and rapid approach to the synthesis of SmII compounds not accessible by other means. Of particular importance is the fact that this approach can be used to produce SmII‐based reductants in a wide range of solvents including alcohols. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2008)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 26 publications
0
24
0
1
Order By: Relevance
“…This discovery demonstrated that lanthanides with extremely high redox potentials are accessible for reductive lanthanide(II) chemistry by their in situ preparation. Although this method has not yet been used in organic synthesis, the potential of this approach has been illustrated by the successful synthetic application of Sm(OTf) 2 [51][52][53] and NdI 2 ,…”
Section: Other Lanthanide(ii) Reagentsmentioning
confidence: 98%
See 1 more Smart Citation
“…This discovery demonstrated that lanthanides with extremely high redox potentials are accessible for reductive lanthanide(II) chemistry by their in situ preparation. Although this method has not yet been used in organic synthesis, the potential of this approach has been illustrated by the successful synthetic application of Sm(OTf) 2 [51][52][53] and NdI 2 ,…”
Section: Other Lanthanide(ii) Reagentsmentioning
confidence: 98%
“…(6)]. [52] Although the redox potential of Sm(OTf) 2 has not been determined, the reagent is capable of mediating transformations analogous to those promoted by SmI 2 . In some cases, the use of Sm(OTf) 2 gives enhanced diastereoselectivities and higher yields for reductive processes.…”
Section: Samarium(ii) Alkoxidesmentioning
confidence: 99%
“…Samarium(II) iodide was prepared by standard methods and titrated prior to use. [10][11][12][13][14] All products were identified using 1 H NMR analysis and comparison with authentic samples. GC and/or GC/MS analysis was used for volatile products.…”
mentioning
confidence: 99%
“…To date, only amalgamated Zn and Zn 0 have been used to chemically reduce Eu III -containing complexes to Eu II -containing complexes in water (McCoy, 1935 ; Ekanger et al, 2016a ; Basal et al, 2017a , b ). However, other chemical reductants, which have been used to reduce other Ln III ions to Ln II ions (Teprovich et al, 2008 ; MacDonald et al, 2013 ; Fieser et al, 2015 ), could be used if the low pH required for the use of zinc metal is undesirable or if the standard electrode potential of the Eu-containing complex is more negative than that of Zn 0 .…”
Section: Synthesis Of Eu II -Containing Complexesmentioning
confidence: 99%